2012
DOI: 10.1186/1471-2369-13-140
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mineral and bone disorder on healthcare resource use and associated costs in the European Fresenius medical care dialysis population: a retrospective cohort study

Abstract: BackgroundSecondary hyperparathyroidism (SHPT) is associated with mortality in patients with chronic kidney disease (CKD), but the economic consequences of SHPT have not been adequately studied in the European population. We assessed the relationship between SHPT parameters (intact parathyroid hormone [iPTH], calcium, and phosphate) and hospitalisations, medication use, and associated costs among CKD patients in Europe.MethodsThe analysis of this retrospective cohort study used records of randomly selected pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
2
4
0
1
Order By: Relevance
“…This study highlights that costs related to health care resource utilization, as already reported in a European Union study 20 and a US study, 21 increased with rising baseline PTH. Confirming the findings of the cost consequences analysis of the FARO survey 22 performed on the overall hemodialysis population, the present study showed that different baseline severity of SHPT in terms of PTH level was associated with different treatment patterns.…”
Section: Discussionsupporting
confidence: 77%
“…This study highlights that costs related to health care resource utilization, as already reported in a European Union study 20 and a US study, 21 increased with rising baseline PTH. Confirming the findings of the cost consequences analysis of the FARO survey 22 performed on the overall hemodialysis population, the present study showed that different baseline severity of SHPT in terms of PTH level was associated with different treatment patterns.…”
Section: Discussionsupporting
confidence: 77%
“…Finally, cost‐effectiveness remains an important consideration in the choice of treatment. Uncontrolled HPT increases the economic burden of patients with secondary HPT undergoing dialysis owing to higher medication and hospitalization costs. Compared with cinacalcet treatment, parathyroidectomy is more cost‐effective in these patients, mainly due to the significant additional cost and chronic use of cinacalcet.…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo pacientes con valores de calcio y fósforo por encima del rango normal también tuvieron incremento en el costo mensual por paciente (51) .…”
Section: Diálisis Y Enfermedad Mineral óSeaunclassified